Analysis of Students Misconceptions on Electrochemistry Material using the Four-Tier Diagnostic Test Instrument - Pebriani*, Novita; Bakti, Iriani; Hamid, Abdul; Rusmansyah, Rusmansyah; Ali, Almubarak; Abrori, Fadhlan Muchlas (Jurnal Pendidikan Sains Indonesia, 2024)
This study was conducted to determine the percentage and causes of student misconceptions in electrochemistry using the Four-Tier diagnostic test instrument. The research was conducted using a quantitative-qualitative descriptive method. The data collection technique was done through written tests with four-tier diagnostic test instruments and non-tests through interviews. The research subjects were students of the 2021 batch of Chemistry Education at FKIP Lambung Mangkurat University Banjarmasin. The results showed that 34% of students experienced misconceptions. Students experienced misconceptions in electrochemistry and electromotive power (DGL) sub-matter by 25.27%; the thermodynamic aspect of electrochemistry experienced the smallest misconception of 7.69%; DGL and temperature by 12.09%; connecting the Nernst equation with pH measurements by 17.58%; concentration cells by 14.29%; electrolysis by 12.64%; and corrosion sub-matter by 10.44%. Misconceptions occur in electrochemical materials because students think that salt bridges play a role in accelerating reactions. Students were confused about determining the relationship between DGL and temperature; and they were less careful in determining whether a chemical reaction is spontaneous or not. In addition, students were less careful in determining the actions of the gilding process.